2014
DOI: 10.1186/1471-2407-14-567
|View full text |Cite
|
Sign up to set email alerts
|

A novel naproxen derivative capable of displaying anti-cancer and anti-migratory properties against human breast cancer cells

Abstract: BackgroundIncreasingly, the role of chronic inflammation and its mediators in tumor generation and progression is gaining importance in the field of cancer research. In this context, candidature of non steroidal anti-inflammatory drugs (NSAIDs) as potential anti-tumor therapeutic agent is being evaluated globally. In the present study we have evaluated the anti-cancer effect of a series of newly synthesized naproxen derivatives on human breast cancer cell lines.MethodsMCF-7 (poorly invasive) and MDA-MB-231 (hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
45
2
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(48 citation statements)
references
References 21 publications
0
45
2
1
Order By: Relevance
“…On the other hand, a large number of studies have showed the effect of chronic inflammation in tumorgenesis, and the role of using non‐steroidal anti‐inflammatory drugs (NSAIDs) as anti‐cancer agents . Although the use of NSAIDs can cause some problems, such as gastrointestinal bleeding and increased cardiovascular (CV) issues, the anti‐inflammatory drug naproxen (Figure ) has fewer CV effects with a possible cardioprotective role in humans.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, a large number of studies have showed the effect of chronic inflammation in tumorgenesis, and the role of using non‐steroidal anti‐inflammatory drugs (NSAIDs) as anti‐cancer agents . Although the use of NSAIDs can cause some problems, such as gastrointestinal bleeding and increased cardiovascular (CV) issues, the anti‐inflammatory drug naproxen (Figure ) has fewer CV effects with a possible cardioprotective role in humans.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Deb et al . reported that some naproxen derivatives have powerful anti‐inflammatory and anti‐tumor properties as they induce an appreciable amount of apoptosis in the TNBC cell line …”
Section: Introductionmentioning
confidence: 99%
“…[84] Progression and metastasis of cancer cells are relatedt ot he PGE 2 level. [86] Because NSAIDs are known to reduce inflammationb yi nhibiting COX enzymes that catalyze intracellular PGE 2 formation, [75] whichi se ffective and safe in ap hase II clinical trial against the growth and progression of prostatec ancer, [87] inhibiting cell migration of human breast cancer cells, [88] we have considered exploring the anticancer properties of these gelator salts. [86] Because NSAIDs are known to reduce inflammationb yi nhibiting COX enzymes that catalyze intracellular PGE 2 formation, [75] whichi se ffective and safe in ap hase II clinical trial against the growth and progression of prostatec ancer, [87] inhibiting cell migration of human breast cancer cells, [88] we have considered exploring the anticancer properties of these gelator salts.…”
Section: Anticancer Activitiesmentioning
confidence: 99%
“…Apart from improvements in solubility, derivatization of NAP also is known to enhance the anticancer activity. For example, IC 50 value of Naproxen sodium salt on MCF7 and MDA-MB-231 cell lines are >5 mM and ~10 mM respectively [68]. There is no consensus in the literature regarding the molecular mechanism of the anticancer activity of NSAIDs.…”
Section: Anticancer Activitymentioning
confidence: 99%